2009
DOI: 10.1002/crat.200900190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stirring speed on the crystallization of calcium carbonate

Abstract: Control over crystal morphology of calcium carbonate (CaCO 3 ) was investigated by simply changing the stirring speeds in the process of CaCO 3 formation. Scanning electron microscopy (SEM) and powder X-ray diffraction (XRD) measurements explore the morphology evolution of CaCO 3 at varying stirring speeds. As the stirring speeds increase, rhombohedral calcite, spherical vaterite, and monoclinic crystal with coexistence of calcite phase and vaterite phase were formed, suggesting a facile control over calcium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Yan et al (2009) examined the effect of the stirring rate on the precipitation of the CaCl2 and Na2CO3 solution with varying stirring rate (50-1,000 rpm). At a lower stirring speed (100 rpm), calcite phase was dominantly observed, and a further increase of stirring speed led to the formation of vaterite.…”
Section: Effect Of Other Factors On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%
“…Yan et al (2009) examined the effect of the stirring rate on the precipitation of the CaCl2 and Na2CO3 solution with varying stirring rate (50-1,000 rpm). At a lower stirring speed (100 rpm), calcite phase was dominantly observed, and a further increase of stirring speed led to the formation of vaterite.…”
Section: Effect Of Other Factors On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%
“…29 Yan et al showed the importance of stirring rate for controlling CaCO 3 polymorphism also without additives. 30 A classical view of ionic growth of CaCO 3 crystals 31 cannot explain the observed behavior, as convection is a macroscopic phenomenon. In addition, the traditional view of nucleation and growth of calcium carbonates was recently challenged by Gebauer et al…”
Section: 24mentioning
confidence: 99%
“…[12] A particle size reduction beyond these values has so far not been achieved, since vaterite was found to become unstable in water below this critical size, leading to a rapid recrystallization to the calcite phase. [13] This recrystallization is due to the growing surface-to-volume ratio and enhanced solubility with decreasing particle size.…”
mentioning
confidence: 99%